EU Institutions: Revisiting Gender Balance and Women’s Empowerment - Gabriela Belova; Albena Ivanova (Laws, 2022)
Equality Gender balance between men and women is one of the most current controversial issues in recent years that provokes a number of debates, questioning whether it really exists or is instead a myth. This article examines how the issue is regulated by European Union (EU) law and to what extent the legal framework is implemented into the current composition and work of European institutions. The trend of women’s empowerment is examined on the example of some of the EU institutions, mainly the European Commission and the European Parliament. The authors point out that, at the moment, three of the institutions included in the single institutional framework of the EU are headed by women—Ursula von der Leyen, Roberta Metsola, and Christine Lagarde—and the European Ombudsman is a woman. This represents an undisputed achievement in the field of gender balance at a higher political level within the EU as well as the appointment of the first-ever commissioner for equality. The newest secondary legislation framework is observed: Directive 2019/1158/EU on work–life balance and the latest development with regard to the female representation on corporate boards (Women on Boards Directive). The article also concludes that while some of the institutions have managed to make steps towards a real gender balance during recent years, not all of the Member States have experienced such progress, and this is evident in the organization and work of the Council of the EU. Although the introduction of quotas for women on company boards has been assessed ambiguously, it represents a necessary action ‘to break the glass ceiling’ and would give a new impetus to women’s empowerment within the EU.